Seven decades of mountain hare counts show severe declines where high‐yield recreational game bird hunting is practised. Issue 6 (13th August 2018) - Watson, Adam; Wilson, Jeremy D.
Abstract: Recreational hunting is widespread and can benefit nature conservation when well‐practised, monitored, and regulated. Management for recreational red grouse Lagopus lagopus scotica shooting on upland heathland in the UK causes conservation conflict because the intensive habitat, predator, and disease management needed to maintain high‐grouse densities for "driven" shooting has detrimental environmental impacts, notably for raptor populations. Sustainable management of mountain hares Lepus timidus scoticus, a game species in the same landscapes, poses a challenge. Control of transmission to grouse of a viral disease, louping‐ill, for which mountain hares are a host, has become an additional motivation to kill mountain hares since research during 1993–2001 suggested that culls might reduce infection rates in grouse. We analysed population trends of mountain hares from spring counts on moorland managed for grouse shooting and on contiguous alpine land. On moorland sites, a long‐term decline (4.6% per annum) from 1954 to 1999 increased to 30.7% per annum from then until 2017, with a density index falling to <1% of initial levels after 2008. Before 1999, declines were associated with conifer planting and were least severe where heather burning characteristic of grouse management was present. Grouse moors had the highest rate of decline after 1999. On alpine sites, the density index increased by 2.0% per annum from 1954 to 2007, then declined by 12.3% per annum but remained within the previous range of variation. Despite lack of evidence that it increases grouse numbers, reduction of louping‐ill transmission to grouse became a more frequent justification for mountain hare culls at a time consistent with it causing these recent, rapid mountain hare declines on grouse moors. Synthesis and applications . Long‐term field counts suggest that intensification of game bird management has resulted in severe, recent declines in mountain hare numbers, exacerbating longer term declines associated with land‐use change. Management practices founded on misinterpretation of earlier research are the probable cause. Regulation of hare culling would provide a framework for formal tests of whether culls affect grouse surpluses. It would also provide an opportunity to examine mountain hare populations' resilience to culls of varying size and seasonal timing. Abstract : Long‐term field counts suggest that intensification of game bird management has resulted in severe, recent declines in mountain hare numbers, exacerbating longer term declines associated with land‐use change. Management practices founded on misinterpretation of earlier research are the probable cause. Regulation of hare culling would provide a framework for formal tests of whether culls affect grouse surpluses. It would also provide an opportunity to examine mountain hare populations' resilience to culls of varying size and seasonal timing.